Strategi Pemasaran Syariah Dalam Meningkatkan Penjualan Keset Pada UD. Aditya Juragan Keset Kecamatan Cikancung Kabupaten Bandung - Siti, Elisa; Tiya Rissa Kamila; Popon Srisusilawati (Lembaga Pusat Penelitian dan Pengabdian kepada Masyarakat (LP2M) Institut Agama Islam (IAI) Al-Qodiri Jember, Jawa Timur Indonesia bekerjasama dengan Kopertais Wilayah 4 Surabaya, 2022)
Abstract This study aims to describe how the Islamic marketing strategy in increasing sales of doormats at UD. Aditya Master Doormat, Cikancung District, Bandung Regency. Recognize the characteristics of the surrounding market as well as the market structure that is profitable for this home-based business in order to remain competitive and survive and be able to compete in the current market in a clean manner. The research method used is a descriptive qualitative method by interviewing the owner of UD. Aditya Master Doormat. Field research procedures that produce written or oral data from the people around who are observed. From the research results, it can be seen from the perspective of Islamic marketing strategy, UD. Aditya Juragan Keset, apart from applying conventional marketing strategies, he also implements sharia marketing strategies which consist of three main points, namely firstly applying Shariah marketing characteristics based on the Qur'an and As-Sunnah; second, the application of business ethics in Islam; third, following marketing according to what has been taught by the Prophet Muhammad, namely Siddiq, Amanah, Fathanah and Tabligh Keywords: Syariah Marketing Strategy, UD. Aditya Master Doormat, Sale.